Penguatan UMKM Milik Desa Melalui Pelatihan Pembuatan Desain Packaging Kemasan - Chandra Kirana; Della Puspita; Ricky Tjhin; Yongkie Setiawan; Dhita Heru Pambudi; Ramanda Salbiyanti (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
Micro, Small and Medium Enterprises (MSMEs) that are developing in Penagan Village, Mendo Barat District, Bangka Regency, Bangka Belitung Islands Province need further guidance. This training aims to provide training and assistance regarding marketing strategies through making designs, namely product packaging, labeling, packaging, and marketing strategies for MSME products. The implementation method used in this activity is by conducting training as well as making designs for product packaging, logos, and so on using the Canva application. The result of this activity is to produce various designs, including attractive packaging so that in the future product marketing will be better and MSME product results will be known by all levels of society, both locally and internationally